Total glossectomy with laryngeal preservation and free flap reconstruction: Objective functional outcomes and systematic review of the literature123. (5th September 2012) - Dziegielewski, Peter T.; Ho, Michael L.; Rieger, Jana; Singh, Prabhjyot; Langille, Morgan; Harris, Jeffrey R.; Seikaly, Hadi
Abstract: Objective: Advanced tongue cancer is a devastating diagnosis with potential for significant morbidity after treatment. This is especially true for patients undergoing total glossectomy with laryngeal preservation (TGLP), free flap reconstruction and adjuvant radiotherapy. The goals of this study were to: 1) determine long‐term objective functional and quality of life outcomes, 2) investigate the influence of rehabilitation on functional recovery and 3) determine swallowing ability in patients with TGLP. Study Design: Prospective cohort study and systematic review of the literature. Methods: Functional outcomes data were collected from 2000–2010. Outcomes were measured pre‐ and 12 months post‐surgery and included: gastrostomy‐tube (G‐Tube) rates, swallowing transit times on video fluoroscopic swallowing studies, speech intelligibility and EORTC‐H&N 35 quality of life scores. A systematic review of the literature was conducted to determine comprehensive long term G‐Tube rates. Results: Twelve patients were included and eight were still living at 12 months post‐surgery. Fifty percent of patients in this study and 24% with systematic review used G‐Tubes at 1 year post‐surgery. Patients who could swallow did not aspirate, but more than doubled swallowing transit times. Spoken sentence intelligibility averaged 66% and mean quality of life scores improved 8.9 points 12 months post‐surgery. Patients who attended >80% of swallowing and speech rehabilitation sessions demonstrated superior swallowing and speech functional outcomes. Conclusions: Although a potentially morbid treatment, TGLP and free flap reconstruction can provide good swallowing and speech outcomes as well as meaningful long‐term quality of life. Regular attendance of rehabilitation sessions is imperative to optimize functional outcomes. Laryngoscope, 2013